Work-Life Balance in Pediatric Orthopaedics: The Role of the LeadersBox 1 – Fostering work-life balance for my team: Corinna Franklin, MDBox 2 – Work-life balance interventions: Rebecca E. Glavin, MBA, MSW, LCSW - Steven L. Frick, MD; Rebecca Glavin, MBA, MSW, LCSW; Corinna Franklin, MD, AB; Peter M. Waters, MD, MMSc (Journal of the Pediatric Orthopaedic Society of North America)
This article describes the intersection of two POSNA initiatives, leadership development and professional well-being, highlighting the role of orthopaedic leaders in helping themselves (by deliberate actions and role modeling) and others (by mentoring, administrating, and promoting well-being programs) work to achieve work-life balance and physician well-being for themselves and those they lead.